Assessing oxygen limiting fermentation conditions for 2,3-butanediol production from Paenibacillus polymyxa - Stoklosa, Ryan J.; Latona, Renee J.; Johnston, David B. (Frontiers in Chemical Engineering, 2022)
2,3-butanediol (2,3-BDO) is a platform chemical that can be converted to a wide array of products ranging from bio-based materials to sustainable aviation fuel. This chemical can be produced by a variety of microorganisms in fermentation processes. Challenges remain for high titer 2,3-BDO production during fermentation due to several parameters, but controlling oxygen is one of the most relevant processing parameters to ensure viable product output. This work investigated the fermentation of plant biomass sugars by the 2,3-BDO producer Paenibacillus polymyxa. Aerobic and oxygen limited fermentation conditions were initially evaluated using molasses-based media to determine cell growth and 2,3-BDO output. Similar conditions were then evaluated on hydrolysate from pretreated sweet sorghum bagasse (SSB) that contained fermentable sugars from structural polysaccharides. Fermentations in molasses media under aerobic conditions found that 2,3-BDO could be generated, but over time the amount of 2,3-BDO decreased due to conversion back into acetoin. Oxygen limited fermentation conditions exhibited improved biomass growth, but only limited suppression of 2,3-BDO conversion to acetoin occurred. Glucose depletion appeared to have a greater role influencing 2,3-BDO conversion back into acetoin. Further improvements in 2,3-BDO yields were found by utilizing detoxified SSB hydrolysate.